How to apply SCRUM in PBL teams - Carvalho, José Dinis (2018)
Scrum is a project management methodology very popular in the software industry with very good results in terms of team work effectiveness. Scrum is based on important team work values such as commitment, courage, focus, openness and respect and can be described in three different dimensions: Scrum team; Scrum Events; and Scrum artefacts. This workshop aims to provide the participants with the opportunity to practice the scrum methodology. This goal will be attained by using a short project which includes similar characteristics to the typical PBL projects. The first moment of the workshop will focus on presenting the basic concepts about the Scrum methodology, its use and main features. In the second moment the participants will be actively involved in a training activity which allows them to practice Scrum in a small project. This includes the generation of a backlog, a sprint planning meeting, and at least on sprint (one iteration of the methodology). The third and last moment will be based on the discussion and reflection about the effectiveness of this methodology when applied in PBL teams. Some guidelines and tips for an effective use of Scrum in PBL teams will be available for all participants on the workshop.